The long-term mine production scheduling problem - SARIN, SUBHASH C.; WEST-HANSEN, JAN (IIE transactions, 2005)
Recognizing the complexity of coal mining management, e.g., the scarcity of financial resources and a variation in the quality of coal found in different sections of a mine, in this paper, we develop a mixed-binary programming model as an aid for generating mine production schedules in order to obtain coal of the desired quality and maximize the associated net present value. The model is based on the definition of the mine layout as a precedence network, with the nodes representing mining sections. A general solution methodology based on the Benders' decomposition of the model is developed. It exploits the special nature of the resulting subproblems in order to develop an effective solution procedure. Computational experience of this procedure, along with the results of its application to a mining case, are presented.